PEER REVIEW - Team, Editorial (Journal of Medicine and Health, 2017)
We would like to thank our peer reviewers for the precious contributions in providing clinical, scientific, and methodological expertise for JMH Volume 1 Number 6. We appreciate every thoughtful review of submitted manuscripts and for making important contributions to improve the scientific quality of articles published in JMH. We listed the names in alphabetical order.Â Adhi Kristianto Sugianli, dr., Sp.PK(K), M.KesAndri Rezano,dr.,M.Kes,Ph.DCindra Paskaria,dr., MKMCherry Azaria,dr., M.KesDrs. Eko Suhartono, M.ScDR.Guswan Wiwaha, dr., MMDR. Hana Ratnawati, dr., M.Kes., PA(K)Hanna, dr., M.Kes., Ph.D., AIFOJuly Ivone, dr., MKK., MPd.KedLarissa, dr., Sp.PK, MMRSDR. Meilinah Hidayat, dr., M.KesDR. Oeij Anindita Adhika,dr., M.Kes., PA(K)Rizna Tyrani, dr., M.KesStella Tinia Hasianna, dr., M.KesDR. Teresa Liliana Wargasetia, S.Si., M.Kes., PA(K)Vinna Kurniawati, drg., M.Kes